Effect of Formaldehyde and Curcumin on Histomorphological Indices, Gene Expression Associated with Ovarian Follicular Development, and Total Antioxidant to Oxidant Levels in Wistar Rats - Farshad, Zahra; Shahedi, Abbas; Fesahat, Farzaneh; Hassanpour, Azam; Anvari, Morteza (International Journal of Biomaterials, 2023)
The present experimental study was undertaken to investigate the effect of formaldehyde (FA) and curcumin (CUR) on histomorphological features, antioxidant potential, and messenger ribonucleic acid (mRNA) levels of genes related to follicular development in FA-exposed rats. 24 Wistar female rats were divided into four study groups and given intraperitoneal injections of FA (10 mg/kg) (N = 6), FA (10 mg/kg) + CUR (100 mg/kg) (N = 6), sham (N = 6), and control (N = 6) for 14 days. Ovarian follicular histology, the related gene expression, blood factors, and anti/oxidation potentials were assessed using ovarian tissue and serum, respectively. The klotho was significantly overexpressed in the FA group compared with controls and shams. Contradictory, the factor in germ line alpha was significantly down-regulated in FA and FA + CUR groups compared to shams and controls. A significant decline was seen in the number of ovarian follicles in the FA group, independent of the developmental stage. Regarding the comparison of the FA + CUR group to other groups, a significant change was seen in the number of secondary, graafian, and atretic follicles. The FA group demonstrated significantly lower hemoglobin, red blood cell count, hematocrit, and mean corpuscular hemoglobin concentration than controls. The activity of glutathione peroxidase increased significantly in the FA group than in the controls. Despite the deleterious effects of FA on histological and molecular aspects of rat ovarian follicles, CUR does not appear to have a protective effect against the hazardous effects of this chemical. However, CUR in some cases has positive effects such as reducing follicular destruction and interstitial edema.